Simulation of formation waviness on working surfaces rings of roller bearings during centerless grinding operations - Чалий, Василь Дмитрович; Мороз, Сергій Анатолійович; Пташенчук, Віталій Віталійович (Technology audit and production reserves, 2015)
In the article was investigated the formation of waviness on working surfaces rings of roller bearings, which causes the appearance of noise and vibration in the bearing units of machines and mechanisms. To establish patterns of appearance of waviness were used some principles of systems theory and mathematic simulation; in particular the establishments of transfer functions, finding the equation of dynamics, usage of Laplace transformations to solve differential equations, building locus diagrams and others. For the purpose of analysis, centerless grinding system, with some simplifications was considered as a linear, continuous, closed dynamic system. On the basis of this was compiled flow-chart of plunge centerless grinding model on rigid shoes, and was found the transfer function. The solution of the system’s characteristic equation revealed influence of waviness on the ground surface and the regeneration process of this waviness on the locus diagram of displacement vector of the workpiece’s center. As the investigation, result established a regularity of change of waviness harmonics depending on the geometry of rigid shoes setting. Management of waviness surface bodies of revolution on centerless grinding operations is an important prerequisite for getting optimum quality parameters of working surfaces of the roller bearing rings and as a result effect on exploitation properties of the bearing, such as noise, durability, and reliability. Using the results of this research will allow choosing such geometry of setting grinding on rigid shoes, which predictably increases or decreases the parameters of a particular harmonic of waviness.